1990
DOI: 10.1093/ndt/5.3.192
|View full text |Cite
|
Sign up to set email alerts
|

Early Changes in Intracranial Pressure During Haemofiltration Treatment in Patients with Grade 4 Hepatic Encephalopathy and Acute Oliguric Renal Failure

Abstract: We measured the intracranial pressure (ICP), using a subdural catheter in nine patients admitted with grade 4 hepatic encephalopathy due to fulminant hepatic failure complicated by oliguric renal failure. Six patients received daily machine haemofiltration and four patients were treated with continuous arteriovenous haemofiltration (CAVHF). The mean ICP increased during the first hour of machine haemofiltration from 9 +/- 1.4 mmHg to 13 +/- 1.8 mmHg (P less than 0.05), and there was a reduction in the mean art… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
49
1
1

Year Published

1991
1991
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(51 citation statements)
references
References 0 publications
0
49
1
1
Order By: Relevance
“…The CVP decreased from 17 mm Hg to 6 mm Hg during CRRT (figure 3). While previous data has shown elevated ICP with initiation of intermittent hemodialysis, 10 this was not observed in our patient. Other advantages offered by the continuous system included volume removal while maintaining stable CVP (6 to 10 mm Hg), constant solute removal, and maintaining electrolytes as desired by the involved teams.…”
Section: Case Reportcontrasting
confidence: 83%
See 1 more Smart Citation
“…The CVP decreased from 17 mm Hg to 6 mm Hg during CRRT (figure 3). While previous data has shown elevated ICP with initiation of intermittent hemodialysis, 10 this was not observed in our patient. Other advantages offered by the continuous system included volume removal while maintaining stable CVP (6 to 10 mm Hg), constant solute removal, and maintaining electrolytes as desired by the involved teams.…”
Section: Case Reportcontrasting
confidence: 83%
“…This rapid change in osmotic gradient between brain tissue and vascular space leads to cerebral edema, which may cause dialysis equilibrium syndrome. 10 Early in the process, relative hypotension and headache may be the only warning symptoms. However, if not corrected, severe acute confusion and seizures can ensue.…”
Section: Case Reportmentioning
confidence: 99%
“…A previous report showed that rapid decrease in plasma osmolality during HD was associated with an increase in ICP. 11 Our patient had a dramatic decrease in serum osmolality on day 16 after HD, compared to previous days on HD (figure e-1 on the Neurology ® Web site at www.neurology.org). Rapid falls in serum osmolality is thought to be responsible for increases in brain edema and ICP crisis, invoking the reverse urea effect.…”
Section: Figure 2 Follow-up Brain Ct Scan Of the Patientmentioning
confidence: 56%
“…4 Although meta-analysis has its limitations, none of the four included studies showed a renal benefit of CRRT. Jacka et al do not discuss why their retrospective study might differ from the available randomized trials.…”
Section: Continuous Renal Replacement Therapymentioning
confidence: 99%
“…Since the best available data do not indicate that dialytic modality influences outcome in critically ill patients, we suggest that the least costly therapy should be used until new randomized trials demonstrate otherwise. 4 CRRT is superior in correcting azotemia and acidosis and is recommended for patients with severe sepsis. 5,6 While we support Tonelli et al in …”
Section: Continuous Renal Replacement Therapymentioning
confidence: 99%